Evaluation of Interleukin-6 Levels in Patients with Type 2 Diabetes Mellitus (IAHS Medical Journal, 2024)
Background: It has been suggested that inflammatory processes play an important role in the pathogenesis of type 2 diabetes. Individuals who develop type 2 diabetes show signs of low-grade inflammation years before disease onset. This low-grade inflammation has been assumed to be implicated in the pathogenetic mechanisms that cause type 2 Diabetes Mellitus. Inflammatory mediators such as the IL-6 family of cytokines have been proposed to be involved in the events that lead to type 2 diabetes. IL-6 has immunoregulatory actions been proposed to affect glucose homeostasis and metabolism directly and indirectly by action on skeletal muscle cells, adipocytes, hepatocytes, pancreatic b-cells and neuroendocrine cells. Many studies have suggested the role of IL-6 in the pathogenesis of type 2 diabetes mellitus. However, no references have been observed in Bangladesh regarding IL-6 and its association with type 2 diabetes mellitus. It thus may highlight the importance of low-grade inflammation in the pathophysiology of type 2 diabetes mellitus. The purpose of this study was to evaluate type 2 diabetes patients' levels of interleukin-6. Materials and methods: A hospital-based cross-sectional observational study was carried out in the Department of Biochemistry Chittagong Medical College, Department of Endocrinology of Chittagong Medical College Hospital and Chattogram Diabetic Hospital. One hundred (100) type 2 diabetes mellitus patient was included in the study by nonprobability consecutive sampling. Important variables in this study were serum IL-6, BMI, waist circumference and duration of Diabetes Mellitus.Results: The mean serum IL-6 level was 10.08±0.39 pg/ml in patients with type 2 Diabetes Mellitus. Serum IL-6 was positively correlated (r 0.33, p